ANALISIS COMMUNITY DEVELOPMENT PT. TELKOM KANDATEL YOGYAKARTA DALAM PENGEMBANGAN UKM MELALUI PROGRAM KEMITRAAN - Suzy Yolanda Gussman; Siti Fathonah; Arif Wibawa (Jurnal Ilmu Komunikasi, 2009)
Corporate Social Responsibility (CSR) is new feature of strongly ethical, humaneness and fully responsible of word business upon its surrounding society. Principally, a company will be unable to growth in the middle hardship environment. Community Development is one of CSR implementation in continual development that encompasses society empowerment. PT. Telekomunikasi Indonesian Tbk. is one company that implicates Community Development through Partnership Program and Environment Establish (PKBL). This program was performed by each Kandatel and PT. Telekomunikasi Indonesian Tbk., as one. This research is proposed to analyze the implementation of Community Development by PT. Telcom Kandatel Yogyakarta to em- power UKM through Partnership Program, to identify the obstacles when performing program, and to identify its advantages for company and program target goal. This research is descriptive research with subjecting on PT. Telcom Kandatel Yogyakarta. Data type that being used are both primary and secondary data. Several techniques that being used to gather data include depth interview, observation and literature study. Data-research and method triangulations were used to extend research validity. Data was analyzed by data reduc- tion, data presentation and conclusion drawn or verification thus research conclusion can be obtained. One of Community Development activities that performed by PT. Telcom Kandatel Yogyakarta is Partnership Program. Partnership Program is program that intended to develop moderate and small business (UKM) activity thus they able to independent. This program had been confirmed by BUMN minister Regulation therefore its procedure and mechanism already determined. During its implementation, three stages that token by PT. Telcom Kandatel Yogyakarta were planning, implementation and evaluation. The successful of Partnership Program cannot directly see from financial that had been given, however, it is can be observed through program continuality. Socialization is one main factor to communicate program existence hence its implementation broadly shared. Partnership Community has high advantage not merely for company but also for Partner Founded. Good image and reputation become main factor in company business live, mean while, Partner Founded has opportunity to develop its business through financial loan and no longer impeded by capital matter.